From Peasant to Peasant: Peasant Education for Agro-Ecological Resistance and Transformation - Valentín Val; Peter Michael Rosset (Universidade Federal do Norte do Tocantins, 2020)
In this essay we address "peasant to peasant" processes (PCaC) as an inclusive educational and epistemic dispositive where an agroecology of knowledges is articulated for the constitution of the agroecological peasantry and peasant agroecology as a process of resistance and transformation from the perspective of rural organizations and social movements articulated in La Via Campesina (LVC).We first introduce an in development about the morphology of the pedagogical processes in PCaC, and then examine three elements that are intimately intertwined in the constitution of the agroecological peasantry: (1) the CaC methodology stricto sensu, (2) peasant schools and processes of education and formation in agroecology, and (3) encounters and organizational processes. Finally, we present some elements to think about how these other pedagogical strategies contribute to the emergence of a diverse and pluralistic agroecological peasantry, and an agroecology that transcends its productive character to become a plural and inclusive political-epistemic-ontological project of agroecological transformation.